Changes in Aqueductal CSF Stroke Volume in Shunted Patients with Idiopathic Normal-Pressure Hydrocephalus - Scollato, A. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Aqueductal CSF stroke volume (ACSV) measured by phase-contrast MR imaging is a tool for selection of surgical patients with idiopathic normal-pressure hydrocephalus (iNPH). The aim of the present study was to investigate whether there is a relationship between clinical outcome and changes in ACSV in patients with iNPH who have been shunted. MATERIALS AND METHODS: Sixty-five shunted patients with iNPH underwent clinical evaluation and ACSV measurements 7–30 days before and 1, 3, 6, and 12 months after surgery. RESULTS: Two patients were excluded from the study for the occurrence of a perioperative complication. In a group of 35 clinically improved patients, the mean preoperative ACSV (157.01 μL) decreased to 18% one month after ventriculoperitoneal shunt (VPS) and ≤49% at 12 months post-VPS. In a group of 15 unimproved patients, the lower mean preoperative ACSV (84.2 μL) decreased to 14.3% one month post-VPS and ≤34% at 12 months post-VPS. In the other 8 improved patients who developed a subdural fluid collection (SDFC), ACSV values decreased by 43%–75% in the 3 months post-VPS. A postoperative ACSV increase was noted in 6 patients with a shunt system malfunction. One patient experienced both SDCF and shunt malfunction. CONCLUSIONS: ACSV decreases in all patients in whom the VPS system works properly, with the rate of ACSV decrease being higher in the patients who show clinical improvement. Postoperative ACSV increase suggests shunt malfunction. A precipitous drop of ACSV values after VPS may be the consequence of increased drainage and herald the occurrence of SDFC.